A tale of two surplus countries: China and Germany - Yin-Wong Cheung; Sven Steinkamp; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2019)
We analyze current account imbalances through the lens of the two largest surplus countries; China and Germany. We observe two striking patterns visible since the 2007/8 Global Financial Crisis. First, while China has been gradually reducing its current account surplus, Germany's surplus has continued to increase throughout and after the crisis. Second, for these two countries, there is a remarkable reversal in the patterns of exchange rate misalignment: China's currency has turned from being undervalued to overvalued, Germany's currency has erased its level of overvaluation and become undervalued. Our empirical analyses show that the current account balances of these two countries are quite well explained by currency misalignment, common economic factors, and country-specific factors. Furthermore, we highlight the global financial crisis effects and, for Germany, the importance of differentiating balances against euro and non-euro countries.
Keywords: F15; F31; F32; 330; Currency Misalignment; Current Account Surplus; Global Imbalances; Global Financial Crisis